Exploring Digital Forensic and Evidence Research Trends: A Comprehensive Data Analysis - Septalia, Alyani Noor; Multazam, Mochammad Tanzil; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article presents a meticulously curated dataset sourced from lens.org, aimed at investigating digital forensic and digital evidence research within the field of law. Through a series of three filtering steps, scholarly works were narrowed down to 125 journal articles published between 2012 and 2022, providing valuable insights for researchers and enthusiasts. The dataset, available on Zenodo, includes CSV and BibTex files, along with nine analytical screenshots. In addition, the analysis conducted via VOSViewer reveals that computer science is the dominant domain discussing these topics, with Graeme Horsman being the most prolific author, contributing 17 documents. It also highlights the correlation between scholarly works and patent citations and identifies the United Kingdom as the most active country in this research domain. Furthermore, Elsevier emerges as the leading publisher with approximately 325 documents. This comprehensive dataset and its associated analysis serve as a valuable resource for scholars and researchers exploring digital forensic and evidence within the legal context.Highlights: Comprehensive Dataset: A curated dataset from lens.org, consisting of 125 journal articles from 2012 to 2022, offers a holistic view of digital forensic research in law. Key Findings: The analysis conducted through VOSViewer uncovers the dominance of computer science, prolific authors, and international contributions in this field. Valuable Resource: The dataset and its analysis provide researchers with a rich source of information for in-depth exploration of digital forensic and evidence within the legal context. Keywords: Digital Forensic, Legal Research, Scholarly Works, Dataset Analysis, VOSViewer